2022
DOI: 10.1038/s41598-022-22749-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional interpretation of miRNAs affected by rare CNVs in CAKUT

Abstract: Rare copy number variants (CNVs) are among the most common genomic disorders underlying CAKUT. miRNAs located in rare CNVs represent well-founded functional variants for human CAKUT research. The study aimed to identify and functionally interpret miRNAs most frequently affected by rare CNVs in CAKUT and to estimate the overall burden of rare CNVs on miRNA genes in CAKUT. The additional aim of this study was to experimentally confirm the effect of a rare CNV in CAKUT on candidate miRNA’s expression and the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…HSALNG0134318 was not identified as a driver lncRNA since only top 20% of tested lncRNAs with enriched targeted miRNAs were selected in this algorithm. Previously, miRNA miR-185 located in 22q11.2 was shown to be associated with CAKUT 32 . Therefore, we further investigated the potential interaction of lncRNAs and miRNAs in 22q11.2.…”
Section: Discussionmentioning
confidence: 99%
“…HSALNG0134318 was not identified as a driver lncRNA since only top 20% of tested lncRNAs with enriched targeted miRNAs were selected in this algorithm. Previously, miRNA miR-185 located in 22q11.2 was shown to be associated with CAKUT 32 . Therefore, we further investigated the potential interaction of lncRNAs and miRNAs in 22q11.2.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xie et al [38] demonstrated that Hcy regulates miR-1929-5p expression, affecting podocyte apoptosis and chronic kidney disease progression. Mitrovic et al [39] found that rare CNVs downregulate hsa-miR484, potentially influencing kidney development and function. Bantounas et al [40] demonstrated, using the model of human embryonic stem cells, that suppression of the miR-199a/214 cluster resulted in glomerular and tubular malformation in renal organoid tissues.…”
Section: Application Of Exosome Mirna In Prenatal Diagnosismentioning
confidence: 99%